2011
DOI: 10.1075/aral.34.1.05adn
|View full text |Cite
|
Sign up to set email alerts
|

‘Ideal-Problem-Solution’ (IPS) Model

Abstract: Research article introductions (RAIs) play a significant role in gaining publication, and therefore have been studied by many applied linguists. Research into RAIs published in Indonesia has begun to be developed (Adnan, 2009; Mirahayuni, 2001; Safnil, 2000), and generally conclude that Indonesian Humanities RAIs were structured differently from English RAIs. However, as these are early studies, their findings still awaits scrutiny, and little information on Indonesian RAIs especially in Education has been pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This study focuses on analyzing the some research article introduction models or styles, applied by Swale in Hartley (2008: 41), Slatcher & Pennebaker's introduction as cited by Hartley (2008;42), Jogthong (2001), Adnan (2011), Jalilifar (2010, Al-Qahtani (2006), Tulu (2009), Ball and Vincent as cited by Woods (1999), and Kalandadze (2007). The analysis styles are on their generic structures.…”
Section: The Scopes Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…This study focuses on analyzing the some research article introduction models or styles, applied by Swale in Hartley (2008: 41), Slatcher & Pennebaker's introduction as cited by Hartley (2008;42), Jogthong (2001), Adnan (2011), Jalilifar (2010, Al-Qahtani (2006), Tulu (2009), Ball and Vincent as cited by Woods (1999), and Kalandadze (2007). The analysis styles are on their generic structures.…”
Section: The Scopes Of the Studymentioning
confidence: 99%
“…Create a Research Space (CARS) from Swales and PJP from Safnil were analyzed by Adnan (2011) in his Ideal-Problem-Solution (IPS) of Research Article Introductions (RAIs). In the results of his research that the possible problems lie in the inappropriate rhetorical patterns found in the introductions of Indonesian research articles, but he only examined the introductions and citations.…”
Section: Rais Developed By Adnanmentioning
confidence: 99%
See 3 more Smart Citations